Paul Dorosh, Bart Minten and Alemayehu Seyoum Taffesse, "Ethiopia's Agri-Food System: Past Trends, Present Challenges, and Future Scenarios" - Dorosh, Paul; Minten, Bart; Taffesse, Alemayehu Seyoum (2020)
Paul Dorosh, Bart Minten, Alemayehu Seyoum Taffesse BOOK LAUNCH Virtual Event - Ethiopia’s agri-food system: Past trends, present challenges, and future scenarios SEP 22, 2020 - 08:30 AM TO 10:00 AM EDT